PENGARUH PEMANFAATAN LIMBAH SANDAL JEPIT TERHADAP PARAMETER MARSHALL PADA CAMPURAN ASPAL PORUS - Darurrizqi, Muhammad; Hartatik, Nurani; Prasetyo, Yudi D. (Jurnal Teknik Sipil dan Arsitektur, 2026)
The rapidly growing industrial sector in Indonesia, ranging from home-based industries to large-scale enterprises, has the potential to generate inorganic waste containing hazardous chemicals that are difficult to decompose and may have adverse impacts on the environment. This study specifically examines waste produced from the slipper manufacturing process by a home-based industry located at Jl. Wadungasri No. 43, Waru, Sidoarjo, as an additive material in porous asphalt mixtures. Porous asphalt is a modern technology within the category of flexible pavement designed to address water puddling issues on road surfaces, owing to its physical structure that contains voids allowing water to pass through. The research methodology employed in this study follows the approach proposed by the Australian Asphalt Pavement Association (AAPA, 2004), in which the Optimum Asphalt Content (OAC) obtained was 4.72%. The testing conducted using an OAC of 4.72% involved substituting waste material into the total mixture with variations of slipper waste content at 0%, 1.5%, 3%, and 4.5%. In accordance with the porous asphalt parameters specified by the Australian Asphalt Pavement Association (2004), at an Optimum Asphalt Content (OAC) of 4.72% and with a recycled flip-flop waste variation of 1.5%, the average Cantabro Loss (CL) obtained was 28.34%, the average Air Flow Density (AFD) was 0.19%, the average Marshall Stiffness (MQ) was 614.1 kg/mm, the average stability was 1217.7 kg, and the average Voids in Mix (VIM) was 20.5%. At an OAC of 4.72% and a waste variation of 3%, the average CL obtained was 33.44%, the average AFD was 0.13%, the average MQ was 621.3 kg/mm, the average stability was 896.2 kg, and the average VIM was 21.5%. At an OAC of 4.72% and a waste variation of 4.5%, the average CL obtained was 36.76%, the average AFD was 0.07%, the average MQ was 529.4 kg/mm, the average stability was 554.6 kg, and the average VIM was 24.9%. Keyword: AAPA 2004, Open Graded, Flip Flops Waste, Marshall Test.